Dissemination of salt tolerant mustard varieties through frontline demonstrations approach for sustainable mustard production in Pali district of Rajasthan - ML Meena; Dheeraj Singh (Journal of Oilseed Brassica, 2026)
Front line demonstrations (FLDs) on mustard were laid down at 565 farmers’ fields to demonstrate production potentialand economic benefits of improved production technologies comprising salinity tolerance varieties namely CS 52, CS 54,CS 56 and CS 58 in Pali district of arid zone of Rajasthan state during Rabi seasons from 2012-13 to 2017-18 in irrigatedfarming situation. The findings of the study revealed that the improved production technologies recorded an additionalyield ranging from 3.6 to 7.9 q/ha with a mean of 5.5 q/ha. The per cent increase yield under improved productiontechnologies ranged from 35.8 to 68.7 (CS 52), 34.3 to 57.9 (CS 54), 37.6 to 65.9 (CS 56) and 61.5 to 67.5 (CS 58) in respectiveyears. The average extension gap, technology gap and technology index were 5.5q/ha, 6.5q/ha and 28.3 per cent,respectively in different salt tolerance varieties of mustard. The improved production technologies gave higher benefitcost ratio ranging from 2.4 to 3.6 with a mean of 2.6 as compared to local checks (1.9) being grown by farmers underlocality. The results revealed that the maximum number of the respondents had medium level of knowledge and extent ofadoption regarding recommended mustard production technology. The study reported lack of suitable salinity toleranceHYV as major constraints by beneficiaries at rank first followed by low technical knowledge. Thus the productivity ofmustard per unit area could be increased by adopting feasible scientific and sustainable management practices with asuitable salinity tolerance variety